Siren's call [large type] : a rainshadow novel - Castle, Jayne (Castle, Jayne. Rainshadow novel., 2015)
"In the alien catacombs of Rainshadow, there are creatures whose compelling songs lure the unwary to their death. That's why Rafe Coppersmith, hired to clear out the catacombs for exploration, needs a music talent. He knows the perfect one, but she probably doesn't want anything do with him. Ella Morgan had once fallen hard and fast for Rafe, but then he disappeared for months and he's not about to tell her why. Ella, too, has secrets that only her dust bunny knows. She's not just a music talent, she's a Siren: a paranormal singer capable of singing men to sleep or to their deaths. But once on Rainshadow, Rafe and Ella will learn that surrendering to passion doesn't come without risks and fighting fire with fire only adds to the flame "--publisher.